Агітаційно-пропагандистська аркушева література Директорії УНР (листопад 1918 р. – січень 1919 р.) - Лук’янець, К. (Сiверянський лiтопис, 2019)
У статті досліджено особливості функціонування листівкових видань, видрукуваних Директорією УНР. Розглянуто агітаційну аркушеву літературу як додаткове
джерело вивчення історії діяльності Директорії в листопаді 1918 р. – січні 1919 р.
Проаналізовано тематику й зміст опублікованих матеріалів у аркушівках. The scientific relevance of the topic of this article is caused by importance of the
study of the sources on the history of the Ukrainian revolution of 1917–1921-th. One of
these sources is the leaflets from the collection of the department of old printed and rare
editions of the Vernadsky National Library of Ukraine. The article deals with the problem
of functioning of leaflets printed by the Directory on the materials of the collection of
leaflets of VNLU. Among this collection are more then 80 copies of one-sheet editions
which have valuable information about the Directory’s activity in November 1918 –
January 1919. The author proves that in 1917–1921-th publication of agitation leaflets
was the mostly popular during the time of the Directorate of Ukraine. Much attention
is given to subject and content of the published materials in one-sheet editions. It was
established that leaflets are mainly devoted to the sharp themes of the military and sociopolitical
life of the Ukrainian People’s Republic. Publicistic essays in the leaflets in which
are mentioned confrontation with Pavlo Skoropadsky, Bolshevik Russia, the formation of
a higher legislative body of the country and its national policy are considered.
The author focuses on the principal state institutions that prepared, issued and distributed
leaflets. It was established that these editions were published by various printing
houses of Kyiv, mainly on request of the Central Information Bureau of the Directory of
the Ukrainian People’s Republic. Attention has been drawn to the typographical particularities
of this one-sheet editions as a type of printed editions of the era of the Ukrainian
Revolution. The visual and informative features the Directory’s leaflets are highlighted.
There are many copies with large sizes among one-sheet editions, which means that they
were focused on the mass reader, for posting in crowded places. The author comes to the
conclusion that leaflets were part of the policy of government informing the population
of the country and ensured the rapid dissemination of the Directory’s political program.